Analysis Of The Implementation Of The Regional Government Report Information System (SILPPD) At The Directorate Of Regional Performance Evaluation And Capacity Improvement (EKPKD) Directorate General Of Regional Autonomy, Ministry Of Home Affairs - Indah Dwi Oktasari; Marja Sinurat; Ahmad Averus Toana (INFOKUM, 2025)
The research began with many local governments not yet optimal in inputting LPPD data and low human resource competency in understanding the input of IKK LPPD through SILPPD. The success of achieving regional autonomy is influenced by the implementation of targeted regional government and guaranteed growth of regional development. To realize this, an evaluation of regional government implementation is carried out through the Regional Government Implementation Report Information System (SILPPD) in assessing the performance of regional government implementation. This study aims to analyze the implementation of SILPPD, analyze the supporting and inhibiting factors in the implementation of SILPPD, and efforts made by the EKPKD Directorate in overcoming inhibiting factors in the implementation of SILPPD using the PIECES analysis theory by James Wetherbe which emphasizes the dimensions of Performances, Information, Economy, Control, Efficiency, Service. This study was conducted using a qualitative research method with an inductive approach. Data sources were obtained from primary and secondary data. Data collection was carried out by observation, interviews, and documentation. Then the data analysis technique is carried out through data reduction, data tabulation, data presentation, and drawing conclusions. The results of the study indicate that the implementation of SILPPD in the EKPKD Directorate has been running well and efficiently according to the aspects measured by the percentage recapitulation using a Likert scale calculation of 79.38%. Supporting factors in the implementation of SILPPD are easy SILPPD mechanisms, laws and regulations, adequate facilities and infrastructure. The inhibiting factors include the lack of understanding of IKK and the presentation of supporting data by the local government, limited features in SILPPD, the absence of clear standards from the Ministry/Institution regarding operational definitions and standard standards for supporting data. Efforts made by the EKPKD Directorate to overcome the inhibiting factors in the implementation of SILLPD are the implementation of technical guidance for SILPPD users, development of the SILPPD application, and updating of Key Performance Indicators (IKK) with the Ministry/Institution.